2016
DOI: 10.1038/srep36461
|View full text |Cite
|
Sign up to set email alerts
|

Functional screening of mammalian mechanosensitive genes using Drosophila RNAi library– Smarcd3/Bap60 is a mechanosensitive pro-inflammatory gene

Abstract: Disturbed blood flow (d-flow) induces atherosclerosis by altering the expression of mechanosensitive genes in the arterial endothelium. Previously, we identified >580 mechanosensitive genes in the mouse arterial endothelium, but their role in endothelial inflammation is incompletely understood. From this set, we obtained 84 Drosophila RNAi lines that silences the target gene under the control of upstream activation sequence (UAS) promoter. These lines were crossed with C564-GAL4 flies expressing GFP under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…[35] Research found that the inducible knockdown of RPN5 had a vital inhibitory effect on Toll and IMD-mediated NF-κB activation, so Rpn5 might be a mechanosensitive NF-κB activator. [36] Study also revealed that the expression of osteopontin and NF-κB elevated in human aortic aneurysms, which accelerate the degradation of the extracellular matrix and play a significant role in pathogenesis and development of TAA and AAA. [37] In addition, intracellular NF-κB signaling played an important role in remodeling of blood vessels and formation of aneurysms.…”
Section: Discussionmentioning
confidence: 89%
“…[35] Research found that the inducible knockdown of RPN5 had a vital inhibitory effect on Toll and IMD-mediated NF-κB activation, so Rpn5 might be a mechanosensitive NF-κB activator. [36] Study also revealed that the expression of osteopontin and NF-κB elevated in human aortic aneurysms, which accelerate the degradation of the extracellular matrix and play a significant role in pathogenesis and development of TAA and AAA. [37] In addition, intracellular NF-κB signaling played an important role in remodeling of blood vessels and formation of aneurysms.…”
Section: Discussionmentioning
confidence: 89%
“…The protein encoded by the SMARCD3 gene is a member of the SWI/SNF protein family. Its members have helicase and ATPase activities and can regulate the transcription of genes by changing the chromatin structure around the genes, playing an important role in physiological processes [13][14][15]. Reports show that SMARCD3 can regulate the cell cycle through the CDKN1A signaling pathway, affecting tumor formation [16], and it can also regulate muscle development in zebrafish through MYOD and MYF5 signaling pathways [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Cell morphology and tumour organisation have been found to be a factor in modulating the intracellular signalling state through pathways able to integrate mechanical stimuli from the extracellular environment (Miralles et al, 2003;Olson and Nordheim, 2010;Orsulic et al, 1999;Zheng et al, 2009). The discovery of mechanosensitive pathways in various tissues has revealed a complex interplay between cell morphology and signalling (Kumar et al, 2016). Further studies have revealed that cell morphology can also be a predictor of tumorigenic and metastatic potential as certain nuclear and cytoplasmic features enhance cell motility and spread to secondary sites (Wu et al, 2020), aided by the Epithelial to Mesenchymal Transition (EMT).…”
Section: Introductionmentioning
confidence: 99%